Effect of carbamoyl phosphate on nitrogenase in Anabaena cylindrica Lemm. - Lawrie, A C (1979)
Carbamoyl phosphate inhibited acetylene reduction by whole cells and cell-free extracts of Anabaena cylindrica. Higher levels of both endogenous carbamoyl phosphate and carbamoyl phosphate synthase activity were present in NH4+-grown cells (in which acetylene reduction was absent) than in N2-grown cells (in which acetylene reduction was present). However, inhibition of acetylene reduction was observed also with cyanate, the main initial decomposition product under the conditions used. It is concluded that carbamoyl phosphate or one of its metabolites may act as a physiological regulator of both nitrogenase activity and synthesis, but caution must be used in interpreting effects observed several hours after the addition of carbamoyl phosphate, because the effects may be due to cyanate.